The Study of Tariff Barriers and Foreign Exchange Rates Effects in the Function of Iran's Import Demand: A Critical Review of Iran's Trade Policy and Foreign Exchange Regime for Real Support to National Production) - Ali Zahedtalaban; Mahdi Khodaparast Mashhadi; Ahmad Sabahi; Mohamadreza Lotfalipour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
So far, relatively a few studies have been conducted to investigate the effect of tariff rates on total imports of countries, which do not have consistent results. In this paper, we examine the actual effects of tariff and currency rates on the import demand function. For this purpose, based on the theory of demand and by applying relevant econometric techniques, we estimated the import demand function and regressed it to gross domestic product (GDP), relative price of imported goods, tariff rates, and the price of currency through the Auto Regressive Distributed Lags (ARDL) method. The results show that the imports have a positive correlation with GDP and a negative correlation with relative prices, exchange and tariff rates which are consistent with the theory. Long-term coefficients obtained are meaningful for all variables except for tariffs, which indicate the lack of long-term effects of tariffs on import demand. This conclusion seems to be paradoxical for Iran, which has one of the most protective tariff regimes in the world. But by reviewing the bottlenecks and shortcomings of trade policy in Iran, in particular by considering inefficiency of foreign exchange policies, we can realize that the actual tariff protection is much less than what isshowon in nominal one, and therefore, the estimated result for tariff effect is justifiable. A list of reforms and recommendation policies in line with real support of the national production are proposed at the end of paper.